A VIEW FROM CHILE DEMOCRATIC CHANGE IN SPAIN. POLITICAL TRANSITION IN MERCURY (1975-1983) - Castellanos López, José Antonio (Revista de Historia Social y de las Mentalidades, 2011)
This article aims to become an approximation to the idea projected in Chile about the transition to democracy in Spain from a very specific view: the one showed in the most important writing media in the country, El Mercurio de Santiago. Through a thorough search in its opinion section and especially the publishing section, we have outlined an overview which attempts to describe how this newspaper assimilated the events which made the authoritarian dictatorial regime of the Spanish state turn into a fully guaranteed democracy and how newspapers poured it onto their readers making it a published opinion. For this purpose, we have been trying to inquire especially into those matters which would be used like an excuse for their ideological position about a double reality: the Spanish political moment marked by political change and the juncture in Chile, immersed in Pinochet’s dictatorship, which was then between its continuity and its institutionalization